Problematika Pembelajaran Spiritual di Lembaga Pendidikan Formal - Syaikhu Rozi; Amil Cholisna Wardah (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2020)
This paper seeks to describe the various problems that need to be resolved by scientists, teachers and other education practitioners who want to implement spiritual learning in formal educational institutions. Based on the analysis and reflection, it can be concluded that spiritual learning in formal educational institutions will encounter several problems including problems in the field of material construction which is the learning material, problems of orientation and educational goals, problems with learning strategies, including problems related to the duties and roles of subject teachers. . These problems must be resolved if spiritual learning is to be carried out in formal educational institutions.